Modelos de atención en tratamientos odontopediátricos, de niños de 2 a 5 años. revision bibliográfica - Mishel Estefanny, Jaramillo Daquilema (2021)
The documentary, cross-sectional, retrospective and descriptive study aimed to analyze the academic publications by means of a bibliographic review on the models of care in pediatric dentistry for children aged 2 to 5 years, whose objective was to determine the main models of health, its characteristics and success stories focused on the area of pediatric dentistry, considering its components and common elements. 90 scientific articles found in different databases such as Google Scholar, Elsevier, Pubmed and Scielo were selected, of which 40 articles were chosen based on the average number of citations and the SJR impact factor, these models had three main components such as : prevention in oral health, promotion, diagnosis and treatment; 20 successful application models were found both in vulnerable and underserved populations, low socioeconomic groups or population related to extreme poverty that generated effective results.